2022
DOI: 10.1055/a-1946-6892
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 5-Year Risk for Revision of the Oxford UKA Using New Instrumentation versus Conventional Instrumentation: A Registry Study of 12,867 UKAs

Abstract: Background and purpose: Microplasty instrumentation was introduced for a more consistent surgical implantation technique, especially component alignment and tibial resection level, of the Oxford medial unicompartmental knee replacement (UKA) and thereby aims to improve UKA survival. This study aimed to assess the 5-year risk for revision and reasons for revision of the Oxford medial UKA using the new instrumentation (Microplasty) with its predecessor, i.e., conventional instrumentation (Phase 3). Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…11,17 Using MP, OUKA has achieved superior clinical and radiologic outcomes. 9,11,18,19 The study by Gaba et al 11 of Indian patients reported excellent short-term outcomes for OUKA with MP, with an average Oxford Knee Score (OKS) of 39.5 ± 5.7, and 91.2% of patients achieved good or excellent OKS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17 Using MP, OUKA has achieved superior clinical and radiologic outcomes. 9,11,18,19 The study by Gaba et al 11 of Indian patients reported excellent short-term outcomes for OUKA with MP, with an average Oxford Knee Score (OKS) of 39.5 ± 5.7, and 91.2% of patients achieved good or excellent OKS.…”
Section: Discussionmentioning
confidence: 99%
“…In OUKAs with MP, malalignment was a less frequent reason for revision compared with conventional OUKAs (7.5% vs 16%; p = 0.001). 18 A study conducted in Italy demonstrated that MP is more effective than OUKA phase 3 in terms of determining the tibial cut and improving the tibial slope. 19 Most patients included in our study fell within the tolerance range for radiographic parameters for both femoral and tibial component positions, which is consistent with findings from previous research.…”
Section: Discussionmentioning
confidence: 99%